Differentiating Benign from Suspicious Vertebral Marrow Lesions Detected with Conventional Magnetic Resonance Imaging Using Apparent Diffusion Coefficient and Diffusion-Weighted Image - Mohson, Khaleel Ibraheem; Naief, Qusay Tayser; Jalil, Farah Abdul (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Advanced magnetic resonance imaging (MRI) sequences, include the apparent diffusion coefficient (ADC) and diffusion-weighted imaging (DWI), are of great benefit in assessing troublesome vertebral marrow lesion in patients presented with primary malignancy outside the spines. OBJECTIVES: The aim of the study was to evaluate the role of vertebral column MRI in characterization and evaluation of marrow lesion in patients with primary malignancy utilizing ADC and DWI in addition to conventional MRI sequences. METHODS: This is a cross-sectional study which includes 80 patients referred to MR unit 58 of them referred from the oncology department in oncology teaching hospital having primary cancer outside the spine and also referred complaining of back pain and worry from metastasis while the remaining 22 are cancer-free patients referred to MRI because of lower back pain – the study was performed in Medical City, Baghdad, Iraq, during the period from the beginning of September 2018–October 2019. RESULTS: The study sample consists of 55 females and 25 males, the breast cancer is main primary in females and represents 30/58 patients, while the prostate is the main cancer in males and represents 7/58 patients. When correlating the MR sequences (T1W, Fat sat and DWI) all together and after addition of ADC value (<9x10-3 mm2/sec) in diagnosis of malignancy there is decreasing frequency of positive cases from 39% before ADC to 22.4% after adding it which is close to histopathology results (17% ). The sensitivity, specificity, positive predictive value, negative predictive value, and overall accuracy of ADC in detecting metastasis within the vertebral marrow are 94%, 95%, 88.9%, 97.5%, and 94.8%, respectively. CONCLUSION: Conventional MRI using standard T1W, T2 weighted, and fat suppression sequences cannot discriminate between benign and pathological vertebral marrow lesions. Using DWI improves the recognition of pathological bony lesion(s) and this is strengthened when enforced by ADC value and by that, it can replace the need for intravenous contrast administration. DWI and ADC are beneficial in follow-up of previously detected restricted lesion and in assessment its response to treatment that was depicted by measuring its ADC that consequently elevated in healing phase.